Survey of psychological resilience among university students majoring in long-term-care–related disciplines in Taiwan - Chia-Chen Chang; Chen-Yin Tung; Su-Hao Fan; Wei-Hsiang Huang (BMC Psychology)
Abstract Background The psychological resilience of university students majoring in long-term-care (LTC)–related disciplines is crucial for workforce retention and effective care provision in this field. This study aims to investigate the differences in levels of psychological resilience among these students in Taiwan. Methods This cross-sectional study involved 258 participants selected via stratified random sampling from 23 universities across Taiwan from November 2021 to November 2022, representing a diverse educational context. The research instrument used was the Resilience Scale for Adults, a validated psychological resilience questionnaire. The independent variables included participants’ demographic data, while the dependent variables encompassed five dimensions of resilience: personal strength, family cohesion, social resources, social skills, future organizational style, and total resilience score. Data analysis was performed using descriptive statistics, independent-samples t-tests, analysis of variance, and multiple regression analysis. Results Participants with LTC work experience and leadership roles in campus clubs demonstrated significantly higher scores in personal strength (LTC: t = 2.04, p = 0.04, d = 0.29; leadership: t = 2.89, p = 0.01, d = 0.45), social resources (leadership: t = 2.47, p = 0.01, d = 0.34), social skills (leadership: t = 4.51, p = 0.01, d = 0.62), and future organizational style (LTC: t = 2.72, p = 0.01, d = 0.39). Higher academic performance was linked to greater personal strength, social resources, future organizational style, and total resilience (F = 4.69–3.12, p < 0.05). Regression analysis confirmed the predictive value of leadership experience and LTC work on various resilience dimensions. These results underscore the importance of practical exposure and extracurricular engagement in fostering resilience. Conclusion Students engaged in club activities, leadership roles, and LTC work displayed higher psychological resilience. Educational institutions should foster club participation, leadership experiences, and partnerships with workplaces to enhance student resilience and professional readiness.